2005
DOI: 10.1161/circulationaha.105.552547
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyltransferase as a Risk Factor for Cardiovascular Disease Mortality

Abstract: the Vorarlberg Health Monitoring and Promotion Program Study GroupBackground-There is evidence from recent studies that ␥-glutamyltransferase (GGT) is likely to be associated with cardiovascular disease (CVD). However, few studies to date with sufficient sample size and follow-up investigated the association of GGT with CVD mortality. Methods and Results-The relation of GGT to the risk of death from CVD was examined in a cohort of 163 944 Austrian adults that was monitored for up to 17 years. To evaluate GGT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
221
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(255 citation statements)
references
References 36 publications
16
221
1
2
Order By: Relevance
“…The latter is supported by studies linking elevated GGT levels directly to increased risk of CVD and all-cause mortality. [1][2][3]36,37 Parallel evidence for indirect effects emerges from studies Fig. 1.…”
Section: Discussionmentioning
confidence: 64%
“…The latter is supported by studies linking elevated GGT levels directly to increased risk of CVD and all-cause mortality. [1][2][3]36,37 Parallel evidence for indirect effects emerges from studies Fig. 1.…”
Section: Discussionmentioning
confidence: 64%
“…This finding clearly indicated that subjects with a high-normal ALT might be susceptible to carotid atherosclerosis. There are many cross-sectional [13][14][15][16] and prospective [9,17,18] studies on the association between NAFLD and intermediate markers of cardiovascular disease or clinical outcomes. These studies have reported that ultrasounddiagnosed liver steatosis or raised serum concentrations of liver enzymes predict an increased risk of cardiovascular disease, independent of several established risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, POPs may have increased potency at a lower body burden in an obesity epidemic, because the toxicity of POPs appears to increase among obese persons [29]. Additionally, other POPs, such as brominated flame retardants and perfluorinated compounds, which are still widely used today, may be as important as the POPs we studied in the pathogenesis of type 2 diabetes [49].…”
Section: Critiques Of the Hypothesismentioning
confidence: 98%
“…However, serum GGT activity within its normal range has also been shown to prospectively predict other clinical outcomes [29][30][31][32][33]. Similarly, in the NHANES dataset, serum POP concentrations were positively associated with the prevalence of the metabolic syndrome, insulin resistance, hypertension, and cardiovascular diseases [34,36].…”
Section: Serum Ggt Activity As a Marker Of Exposure To Popsmentioning
confidence: 99%